An abnormal bone lesion of the scapula in a collegiate basketball player: a case report - O'Brien, M. S.; Donnell, A.; Miller, J.; Iven, V. G.; Pascale, M. (Journal of Athletic Training, 2013)
Objective: To present the case of a bone lesion of the scapula in a collegiate basketball player. Background: A 19-year-old National Collegiate Athletic Association Division I male basketball player presented with pain in the posterior region of the right shoulder. During practice, he was performing a layup when his arm was forced into hyperflexion by a defender. Evaluation revealed a bone lesion involving the scapular spine and base of the acromion. Differential Diagnosis: Acromioclavicular joint sprain, subacromial bursitis, subscapular bursitis, humeral head contusion, acromial fracture. Treatment: The patient was treated for 2 months with therapeutic modalities and rehabilitation exercises. Because of persistent pain and the risk of a pathologic fracture, open surgical biopsy and bone grafting were then undertaken. Uniqueness: Most simple bone cysts affect the proximal humerus and femur, whereas our patient's lesion was in the acromial complex. Conclusions: Athletic trainers should be alert to the unusual possibility of bone cysts, which are usually identified incidentally when radiographs are obtained for other reasons. Most simple bone cysts are asymptomatic, but a pathologic fracture can occur with trauma.